Chic Show as a space for expression of fashion and style for the black population of São Paulo in the 1970s and 1980s (ModaPalavra e-periódico, 2025)
This study aims to report how those attending black and soul parties promoted by the Chic Show dance team dressed in the 1970s and 1980s, the company’s peak period. At the same time, it aims to understand how these parties were important in highlighting the self-affirmation and identity of a young black population. To answer these questions, bibliographic and documentary research served as the basis for collecting reports and impressions. Based on this research, it can be concluded that these were dances that were held by black people for black people with the initial intention of providing leisure for this community, but also a meeting point between equals.
Keywords: Chic Show; afro São Paulo fashion and style; black party